2022
DOI: 10.3390/fluids7020075
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Aerodynamic Performance of Bristled Insect Wings Depending on Reynolds Number in Flapping Flight

Abstract: Insect wings are generally constructed from veins and solid membranes. However, in the case of the smallest flying insects, the wing membrane is often replaced by hair-like bristles. In contrast to large insects, it is possible for both bristled and membranous wings to be simultaneously present in small insect species. There is therefore a continuing debate about the advantages and disadvantages of bristled wings for flight. In this study, we experimentally tested bristled robotic wing models on their ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The wing's feathering angle was 45° during the up and down strokes and 0° (vertical position) at the stroke reversals. Mean Reynolds number based on wing length and wing tip velocity was ~ 3.4 in all experiments (Engels et al 2021;O'Callaghan et al 2022) and fluid temperature ~ 24 °C.…”
Section: Wing Design and Kinematicsmentioning
confidence: 96%
See 4 more Smart Citations
“…The wing's feathering angle was 45° during the up and down strokes and 0° (vertical position) at the stroke reversals. Mean Reynolds number based on wing length and wing tip velocity was ~ 3.4 in all experiments (Engels et al 2021;O'Callaghan et al 2022) and fluid temperature ~ 24 °C.…”
Section: Wing Design and Kinematicsmentioning
confidence: 96%
“…Compared to solid wing aerodynamics, there is relatively little known about aerodynamic performance of bristled wings and the flow structures associated with these morphological modifications. A previously published study on model wings with different bristle spacing has shown that lift coefficients decrease with increasing bristle spacing in a non-linear fashion (O'Callaghan et al 2022). At a relative bristle spacing of 0.08 wing length (solid wing, 1.0), a bristled wing loses the ability to produce positive lift while drag is pronounced, yielding drag coefficients around 3.0 due to viscous friction.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations